Barriers to Covid-19 RT-PCR Testing in Indonesia: A Health Policy Perspective - Sucahya, Purwa Kurnia (UI Scholars Hub, 2020)
Indonesia has been facing a hard time accelerating the number of laboratory capacity. This study provides an overview of the data on daily tests, confirmed cases, and the challenge of Covid-19 control associated with government policy. This study utilizes data reported from 2 March to 29 April 2020 by online official sources and regulations. Initially, the government only trusted one lab for the Covid-19 test. As the number of cases increased, referral labs were increased, until 29 April 2020, there were 89 officially appointed laboratories. The daily number of testing results fluctuated and unstable, although the number of reference labs increases. This reflects implementation challenges from different factors: readiness and capacity between labs; availability of swab collection officers; availability of reagents in the lab; rules for lab officers and swab collection officers; and transportation for a specimen from health facility to the referral lab. This study recommends to ensure the lab readiness in terms of human resources, tools, and reagents when appointed; ensure the adequacy and quality of qualified laboratory staff & swab collectors; ensure adequate reagents for RT-PCR, and rearrangement of shift rules for lab & swab collection officers, and improve handling procedures and transport specimen delivery mechanisms.